ANALISIS KOLABORASI STAKEHOLDER DALAM PENGELOLAAN DAYA TARIK WISATA MAKAM SUNAN GIRI GRESIK - Zulfikar Achmad Nur Wachid; Leily Suci Rahmatin (Journal Publicuho, 2024)
This research aims to analyze the collaboration between stakeholders in managing the tourist attraction of the Sunan Giri Tomb in Gresik, one of Indonesia's important religious tourism destinations. The research method used is a qualitative approach with data collection techniques through interviews, observation and documentation studies. The Sunan Giri Tomb Foundation focuses on preserving historical and cultural values. The village government supports it by constructing infrastructure and community empowerment, while the local community participates in various religious and traditional activities. However, this research also identified challenges, such as limited infrastructure, lack of optimal promotion, and competition with other religious tourism attractions. Therefore, a more integrated collaborative strategy is needed to strengthen tourism management, increase attractiveness, and support the sustainability of the development of the Sunan Giri Tomb as a highly competitive religious tourism destination.